PERBANDINGAN EFEKTIVITAS KOMUNIKASI ANTARA ORANG TUA DAN GURU DALAM MEMBANGUN KARAKTER SISWA - Rahmayanti, Irma (Sipakainge: Inovasi Penelitian, Karya Ilmiah, dan Pengembangan (Islamic Science), 2024)
Communication is aprocess whereby a person or several people, groups, organizations, and society related information in order to connect with the environment and other poeple. Educationis the internalization of values in the process of human development which has implications for the formation of character which leads to human behavior. Building character is an effort to imrpove, foster, and shape character so that later they are born as human beings with good character. Communication is a method in the process of character building, meaning that in building character, effective communication is needed. This paper describe a comparison of the effectiviteness of communication between parents and teachers in building student character, especially for fifth grade students at sdn 11 Parepare.